PENGARUH PENGEMBANGAN PROGRAM DESA WISATA TERHADAP PENINGKATAN PENDAPATAN MASYARAKAT BANTUL (STUDI KASUS: DESA WISATA TEMBI TIMBULHARJO KAPANEWON SEWON BANTUL DIY) - Rofik, Mochamad; Wahyuning, Sri; Nugroho, Himawan Agung; Anwar, Andi Rozihan; Wahyudiyono (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2024)
This study was conducted with the aim to analyze the development of tourism village programs in their effect on increasing community income, focusing on Tembi Timbulharjo Kapanewon Sewon Bantul DIY Tourism Village. In this study, quantitative methods with a descriptive approach were used. Primary data was collected through the distribution of questionnaires to the people of Tembi Tourism Village with a total sample of 91 people collected through the random sampling method. Then analyzed with a multiple linear regression analysis model and produced findings that proved that the community participation variable (X1) and facility variable (X2) did not have a partial influence on increasing community income (Y), but the training variable (X3) and promotion variable (X4) had a partial influence on increasing community income. Meanwhile, simultaneously the variables of community participation (X1), facilities (X2), training (X3), and promotion (X4) have a significant influence on increasing community income (Y) in Tembi tourism village.